SCIENTIFIC REVIEW OF THE STUDY TITLED: ADMINISTRATIVE DISCRETION: BETWEEN TEXTUAL JUSTIFICATİONS AND PRACTICAL FEATURES - Munaf Fadhil Challoob (American Journals Publishing, 2026)
This paper presents a critical analytical review of the study titled "Administrative Discretion: Between Textual Justifications and Practical Features." While the original study successfully grounded the theoretical justifications for granting discretion to the administration, this review highlights a critical gap regarding the practical application within the Iraqi administrative judiciary. The paper addresses the lack of detailed judicial controls in the original work by analyzing the stance of the Iraqi legislator, who, under Article (7) of the State Council Law, has granted the judiciary broad jurisdiction that extends beyond traditional "annulment" to include the power of "modification." The review concludes that "appropriateness" (Mula'ama) in the Iraqi legal system is no longer merely discretionary but has become an integral element of legality. Consequently, administrative discretion is subject to strict judicial review, allowing the judge to substitute the administration's decision to ensure justice and protect rights.
Keywords: Administrative Discretion, Judicial Review, Iraqi State Council, Appropriateness (Mula'ama), Decision Amendment, Employee Judiciary, Legality.